Global Proteomic Analysis of Lysine Malonylation in Toxoplasma gondii - Nie, Lan-Bi; Liang, Qin-Li; Du, Rui; Elsheikha, Hany M.; Han, Nai-Jian; Li, Fa-Cai; Zhu, Xing-Quan (Frontiers in Microbiology, 2020)
Lysine malonylation (Kmal) is a new post-translational modification (PTM), which has been reported in several prokaryotic and eukaryotic species. Although Kmal can regulate many and diverse biological processes in various organisms, knowledge about this important PTM in the apicomplexan parasite Toxoplasma gondii is limited. In this study, we performed the first global profiling of malonylated proteins in T. gondii tachyzoites using affinity enrichment and LC-MS/MS analysis. Three experiments performed in tandem revealed 294, 345, 352 Kmal sites on 203, 236, 230 malonylated proteins, respectively. Computational analysis showed the identified malonylated proteins to be localized in various subcellular compartments and involved in many cellular functions, particularly mitochondrial function. Additionally, one conserved Kmal motif with a strong bias for cysteine was detected. Taken together, these findings provide the first report of Kmal profile in T. gondii and should be an important resource for studying the physiological roles of Kmal in this parasite.